OrthoInspector 3.0: open portal for comparative genomics. Issue Volume 47:Issue D1(2019) (31st October 2018) - Nevers, Yannis; Kress, Arnaud; Defosset, Audrey; Ripp, Raymond; Linard, Benjamin; Thompson, Julie D; Poch, Olivier; Lecompte, Odile
Abstract: OrthoInspector is one of the leading software suites for orthology relations inference. In this paper, we describe a major redesign of the OrthoInspector online resource along with a significant increase in the number of species: 4753 organisms are now covered across the three domains of life, making OrthoInspector the most exhaustive orthology resource to date in terms of covered species (excluding viruses). The new website integrates original data exploration and visualization tools in an ergonomic interface. Distributions of protein orthologs are represented by heatmaps summarizing their evolutionary histories, and proteins with similar profiles can be directly accessed. Two novel tools have been implemented for comparative genomics: a phylogenetic profile search that can be used to find proteins with a specific presence-absence profile and investigate their functions and, inversely, a GO profiling tool aimed at deciphering evolutionary histories of molecular functions, processes or cell components. In addition to the re-designed website, the OrthoInspector resource now provides a REST interface for programmatic access. OrthoInspector 3.0 is available athttp://lbgi.fr/orthoinspectorv3 .